STRUKTUR INSTRINSIK NOVEL KEPANGGANG WIRANG TIWIEK SA DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA JAWA DI SMA - Lanua, Rhian Ardila Maretin; Saddhono, Kundharu; Supana, Supana (Center of Language and Cultural Studies, 2017)
This study describes intrinsic structure of the Novel of Kepanggang Wirang (Burned Above the Shame) by Tiwiek SA and its implication to Javanese teaching at SMA. This study is qualittaive research and applied psychoanalysis as the research design. Data were collected using content analysis and interview. The study revealed that structural parts of the novel included: characters, plots, setting, theme, title, point of view, style and tone, symbolism, and irony. In addition, Kepanggang Wirang is relevant to teaching Javanese in SMA as its language and education values are in support to Basic Competence in SMA Curriculum.